Overview effect of biodiesel storage on properties and characteristics - Zakaria, Hanis; Khalid, Amir; Sies, Mohamad Farid; Mustaffa, Norrizal (Trans Tech Publications, 2014)
Abstract. Biofuels based on vegetable oils offer the advantage being a sustainable and environmen-tally attractive alternative to conventional petroleum based fuel. The key issue in using vegetable oil-based fuels is oxidation stability, stoichiometric point, bio-fuel composition, antioxidants on the degradation and much oxygen with comparing to diesel gas oil. This provides a critical review of current understanding of main factor in storage method which affecting the biodiesel properties and characteristics. In the quest for fulfill the industry specifications standard; the fuel should be stored in a clean, dry and dark environment. Water and sediment contamination are basically housekeep-ing issues for biodiesel. Degradation by oxidation yields products that may compromise fuel proper-ties, impair fuel quality and engine performance. The effect of storage method on the fuel properties and burning process in biodiesel fuel combustion will strongly affects the exhaust emissions.